Volatility spillovers among oil and stock markets in the US and Saudi Arabia - FINTA, Marinela Adriana (Institutional Knowledge at Singapore Management University, 2019)
In this article, we use high frequency data and an identification via changes in volatility approach to assess the volatility spillovers among oil and the US and Saudi Arabian stock markets. We document the existence of asymmetry in contemporaneous spillover effects. Particularly, during the times when oil’s trading hours overlap with the US and Saudi Arabian stock markets, the volatility spillover from oil to the stock markets is higher than the other way around. We highlight the importance of taking into consideration the information present during continuous trading hours of oil, especially during simultaneous trading hours with the stock markets. We compare our findings based on our structural VAR with those of a traditional reduced-form VAR, and observe that contemporaneous and intraday effects are necessary to be taken into account since the indirect transmission of volatility occurs through them.